2021
DOI: 10.2147/ndt.s300893
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Uric Acid Levels and Cognitive Function in Patients with Ischemic Stroke and Transient Ischemic Attack (TIA): A 3-Month Follow-Up Study

Abstract: Purpose Cognitive impairment is a common complication after stroke and transient ischemic attack (TIA). The relationship between serum uric acid (SUA) and post-stroke cognitive impairment (PSCI) is controversial. This study evaluated the association of different SUA levels in the normal range and PSCI at 3 months. Patients and Methods A total of 1523 patients with ischemic stroke/TIA were recruited from the Impairment of Cognition and Sleep (ICONS) subgroup of the China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Evaluation of cognitive function after AIS was performed during the hospitalization in six studies 20 22 24 25 26 27 , and during follow-up after discharge in the other five studies 21 23 28 29 30 . Diagnosis of PSCI was based on the Mini-mental State Examination (MMSE) in two studies 20 28 , the Montreal Cognitive Assessment (MoCA) in seven studies 21 22 24 25 26 29 30 , and MMSE or MoCA in one study 27 . The other study reported two datasets of serum UA values for PSCI diagnosed with MMSE and MoCA, separately 23 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Evaluation of cognitive function after AIS was performed during the hospitalization in six studies 20 22 24 25 26 27 , and during follow-up after discharge in the other five studies 21 23 28 29 30 . Diagnosis of PSCI was based on the Mini-mental State Examination (MMSE) in two studies 20 28 , the Montreal Cognitive Assessment (MoCA) in seven studies 21 22 24 25 26 29 30 , and MMSE or MoCA in one study 27 . The other study reported two datasets of serum UA values for PSCI diagnosed with MMSE and MoCA, separately 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies 25 26 27 29 30 with 2679 patients with AIS reported the risk of PSCI comparing between AIS patients with higher versus lower serum UA at admission. Pooled results showed that higher serum UA was associated with PSCI in patients with AIS (OR: 1.33, 95% CI: 1.02 to 1.73, p=0.04; I 2 =72%; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations